Great expectations? GPs’ estimations of time required to deliver BMJ’s ‘10 minute consultations’ - Nigel Taylor; Jessica Watson; Carol Sinnott; Lesley Smith; Alice M Harper; Stephen Henry Bradley; Harriet Delap; Helen Pyke; James Girkin (BMJ Open)
Objectives To estimate the time required to undertake consultations according to BMJ’s 10-minute consultation articles.To quantify the tasks recommended in 10-minute consultation articles.To determine if, and to what extent, the time required and the number of tasks recommended have increased over the past 22 years.Design Analysis of estimations made by four general practitioners (GPs) of the time required to undertake tasks recommended in BMJ’s 10-minute consultation articles.Setting Primary care in the UK.Participants Four doctors with a combined total of 79 years of experience in the UK National Health Service following qualification as GPs.Main outcome measures Median minimum estimated consultation length (the estimated time required to complete tasks recommended for all patients) and median maximum estimated consultation length (the estimated time required to complete tasks recommended for all patients and the additional tasks recommended in specific circumstances). Minimum, maximum and median consultation lengths reported for each year and for each 5-year period.Results Data were extracted for 44 articles. The median minimum and median maximum estimated consultation durations were 15.7 minutes (IQR 12.6–20.9) and 28.4 minutes (IQR 22.4–33.8), respectively. A median of 17 tasks were included in each article. There was no change in durations required over the 22 years examined.Conclusions The approximate times estimated by GPs to deliver care according to 10-minute consultations exceed the time available in routine appointments. ‘10 minute consultations’ is a misleading title that sets inappropriate expectations for what GPs can realistically deliver in their routine consultations. While maintaining aspirations for high-quality care is appropriate, practice recommendations need to take greater account of the limited time doctors have to deliver routine care.